2012
DOI: 10.1097/shk.0b013e318254d3fb
|View full text |Cite
|
Sign up to set email alerts
|

Direct Protective Effects of Dexmedetomidine Against Myocardial Ischemia-Reperfusion Injury in Anesthetized Pigs

Abstract: Systemic administration of α2-adrenergic agonists has been shown to protect ischemic myocardium, but the direct effects on ischemia-reperfused myocardium have not yet been clarified. This study was carried out to determine the effects of intracoronary dexmedetomidine (DEX) on the myocardial ischemia-reperfusion injury in anesthetized pigs. In open-chest pigs, the left anterior descending coronary artery was perfused through an extracorporeal circuit from the carotid artery. They received intracoronary infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 32 publications
0
46
0
2
Order By: Relevance
“…This molecule also provides protection from ischemia/reperfusion injury [96]. These properties of dexmedomidine led to a study of its eicacy in sickle mice, and Calhoun et al found that transgenic sickle mice receiving dexmedomidine had improved analgesia [97].…”
Section: Other Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…This molecule also provides protection from ischemia/reperfusion injury [96]. These properties of dexmedomidine led to a study of its eicacy in sickle mice, and Calhoun et al found that transgenic sickle mice receiving dexmedomidine had improved analgesia [97].…”
Section: Other Targetsmentioning
confidence: 99%
“…Dexmedetomidine, a speciic 2 -adrenoreceptor agonist, provides anti-nociception independent of opioid receptor action and via inhibition of sensory neurons [96]. This molecule also provides protection from ischemia/reperfusion injury [96].…”
Section: Other Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several animal studies showed that hind limb I/R injury affected several organs, including the kidneys, liver and lungs. [3][4][5] The highly selective and potent a2-adrenergic agonist dexmedetomidine (DXM) is an effective sedative, anxiolytic, and analgesic agent 6 with protective effects against I/R injury in several organs, including the heart, 7 brain, 8 and kidneys, 9 probably due to the antioxidant and anti-inflammatory properties of the compound. [10][11][12] Curcumin (CUR) has a long history of therapeutic use in Indian and Chinese medicine and has several pharmacological properties, including antioxidant, anti-inflammatory, antiviral, antimicrobial, antifungal, as well as anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidence suggests that induced autonomic nervous system modulation during perioperative administration of DEX is associated with a trend towards improved cardiac outcomes following non-cardiac surgery. [1][2][3][4] Previous experiments on animals have shown the benefits of DEX administration in the ischemic heart. [5][6][7] Cardioprotective effects have also been reported in global ischemia of isolated rat hearts.…”
Section: Introductionmentioning
confidence: 99%